Perlindungan Hukum Bagi Peserta Didik Program Pendidikan Dokter Spesialis Dari Tindakan Bullying Di Rumah Sakit - Rahmi, Maulidya; Mulyati, Nani; Kurniawan, Iwan (Lareh Law Review, 2025)
The Instruction of the Minister of Health of the Republic of Indonesia Number HK.02.01/MENKES/1512/2023 was issued to prevent and deal with bullying of students in teaching hospitals. Even though it has been enforced, cases of bullying against students of the specialist medical education program (PPDS) still occur. This study aims to find out prevention and legal protection efforts for PPDS students and their inhibiting factors, with a case study at Dr. M. Djamil Padang Hospital. The method used is an empirical juridical approach, which is to analyze legal practice in the field and relate it to applicable regulations. The results of the study show that the efforts made include: the implementation of the Instruction of the Minister of Health and the Decree of the Minister of Health on the ASN code of ethics, the implementation of SOPs and hospital codes of ethics, periodic socialization every six months, and the provision of facilities for reporting bullying. The main obstacles in this effort are the culture of bullying that is considered a tradition and the fear of PPDS students to report because they are worried that it will have an impact on their studies. Keywords : Legal Protection, Specialist Doctor Education Program, Bullying